PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA PERUSAHAAN - Taufiq Jibu (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
This research aims to examine the effect of intellectual capital on firm’s performance. Intellectual capital is measured through VAIC method, which has three components, namely human capital efficiency, structural capital efficiency and capital employed efficiency. Meanwhile, company's performance is measured using ROE (Return on Equity), Employee Productivity and Tobin's Q. The samples in this research is determined through random complex in the form of cluster sampling, resulting 205 companies from all sectors listed in Indonesia Stock Exchange during the period of 2011-2014. The results of this study demonstrate that human capital efficiency and capital-employed efficiency have positive effects on ROE, Employee productivity, and Tobin's Q. The structural capital efficiency affects Employee Productivity negatively. This result shows that companies in Indonesia still relies on physical assets as measured by capital employed efficiency followed by human capital efficiency in creating added value for the company, which ultimately increase the company’s performance.Keywords: intellectual capital, profitability, productivity, market performance